Inhibition of the decrease of volatile esters and terpenes during storage of wines and a model wine medium by wine phenolic extracts - Lambropoulos, Ioannis (Array, 2007)
The effect of red wine phenolic extracts on the stability of wine volatile esters and terpenes was examined. Muscat (white) and Xinomavro (red) wines were enriched with each extract at 120 or 200 mg/L, and stored in open bottles at 20 °C for 3 and 2.5 days, respectively. Moreover, a model wine medium containing isoamyl acetate, ethyl hexanoate and linalool was enriched with each extract at 100 mg/L, and stored in sealed bottles at 20 °C for 45–90 days. All samples were analysed for volatiles using SPME along with GC-MS analysis. Phenolic composition of wine extracts was determined using HPLC-DAD. No effect on the concentration of any volatiles was observed as a result of the addition of each extract in each wine or the model medium. A wine extract rich in phenolic acids and another one rich in anthocyanins and flavanols inhibited the decrease of volatile esters and terpenes in one or both wines and the model medium. Among them were several important for the aroma of wine such as ethyl acetate, isoamyl acetate, ethyl hexanoate, ethyl octanoate, ethyl decanoate and linalool. The results presented here indicate that wine phenolic acids, and anthocyanins or flavanols may be taken into account as potent inhibitors of the disappearance of volatile esters and terpenes in wines